Penyuluhan Upaya Pencegahan Dan Deteksi Dini Terhadap Permasalahan Nyeri Lutut Pada Masyarakat Wonolopo Mijen - Syurrahmi Syurrahmi; Purna Luberto; Anisa Mutiara Hanani; Eriga Yessyra Syafitri; Cintya Putri Anisah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Public Health is a part of science that discusses and studies the prevention and treatment of diseases in each individual. Some disease conditions found in the community are complaints of knee pain and back pain. The knee pain that is commonly found is Osteoarthritis. Osteoarthritis is the most common form of arthritis, suffered by millions of people worldwide. It is a degenerative joint disease that affects many joint tissues. This problem arises when the protective cartilage at the ends of bones deteriorates over time. Osteoarthritis is usually experienced in the age of 40-60 years. This is due to the advanced age of the degeneration process. In addition to Osteoarthritis, diseases of the shoulder are also found, such as spasm and Triger Point in the upper trapezius muscle. One of the interventions or modalities provided by infrared or infrared physiotherapy. Infrared is one of the Physiotherapy modalities in providing services to patients with the aim of causing relaxation effects and decreasing pain. Infrared is a peacock wave that can relieve pain and stiffness in joints and muscles. The process of vasodilation of blood vessels produced by infrared rays can accelerate the removal of several pain-stimulating chemicals including bradykinin, serotonin, histamine, and proteolytic enzymes. As well as prostaglandins and substance P which increase the sensitivity of the ends of pain fibers, so that in the end infrared can reduce pain intensity. In addition to being given Physiotherapy Interventions also provide Socialization or counseling to the community in accordance with the conditions complained of. Providing explanations related to the conditions or complaints of each community by providing education and home programs.